2017
DOI: 10.1016/j.tjog.2016.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of validity of echogenic intracardiac foci for calculating the risk of Down syndrome in the second trimester of pregnancy

Abstract: Echogenic intracardiac foci are a second trimester marker associated with aneuploidy in high-risk populations. The objective of this study is to assess the validity of echogenic intracardiac foci for Down syndrome detection in the second trimester ultrasound scan. A systematic search in major bibliographic databases was carried out (MEDLINE, EMBASE, CINAHL). Twenty-five studies about echogenic intracardiac foci were selected for statistical synthesis in this systematic review. Those 25 considered to be relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 42 publications
2
10
0
2
Order By: Relevance
“…Thus, we calculated that the percentage of heart defects in the total population in this study was 6.25%, higher than the 0.8% observed in the general population (Prefumo et al, 2003). This was consistent with previous reports, suggests that EIFs in fetuses may be associated with the presence of heart defects (Lorente et al, 2017;Guo et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, we calculated that the percentage of heart defects in the total population in this study was 6.25%, higher than the 0.8% observed in the general population (Prefumo et al, 2003). This was consistent with previous reports, suggests that EIFs in fetuses may be associated with the presence of heart defects (Lorente et al, 2017;Guo et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…This result was relatively higher than expected and may be that the population underwent re-examination after birth including cases with persisted EIFs throughout the pregnancy. It is reported that 8-75% of EIFs disappear as gestation progresses (Arda et al, 2007;Lorente et al, 2017); a similar percentage was found in our study, in which 72.73% of EIFs could not be detected in re-emanations after invasive prenatal diagnosis. Thus, we calculated that the percentage of heart defects in the total population in this study was 6.25%, higher than the 0.8% observed in the general population (Prefumo et al, 2003).…”
Section: Discussionsupporting
confidence: 91%
“…In this study, 65 fetuses with hyperechogenic bowel had normal karyotyping analysis results, but three fetuses with hyperechogenic bowel had abnormal CNVs. At present, many studies reported that fetuses with echogenic intracardiac focus did not have an increased risk for chromosomal abnormalities [18][19][20], but one pathogenic CNV was detected in 22 fetuses with echogenic intracardiac focus in this study. Therefore, SNP array should be considered when karyotyping analysis is carried out for fetuses with mild tricuspid regurgitation, hyperechogenic bowel, and echogenic intracardiac focus.…”
Section: Discussionmentioning
confidence: 45%
“…The higher rate of invasive procedures in group 2 than in group 1 may be related to maternal anxiety. The ultrasound findings of soft markers could be wrongly evaluated as structural malformations by the mothers, which could increase the rate of invasive procedures [4,17]. Even though the mothers were informed that soft markers are seen at higher rates in fetuses with no structural abnormalities and that they are weakly related with the risk of chromosomal abnormalities, some understood this as a higher risk situation.…”
Section: Discussionmentioning
confidence: 99%